Community Empowerment Based on Food Processing Technology Tempe Becomes Tempe Stick - Alina Hizni; . Sholichin; . Samuel (Institut Pertanian Bogor, 2018)
Tempe is one of the processed products of soybeans. Tempe can be further processed into tempe stick by the community through science and technology based entrepreneurship. The targets of this activities are community empowerment in product development, entrepreneurship training and earning extra income. The output of this activities is the diversification of food in the form of healthy food products such as tempe stick. The activities consists of 1) preparation stage (Formulation of formula, analysis of nutritional content of best formula, and manufacture of packaging design and product label); 2) Implementation stage (Entrepreneurship Training, Practice of making tempe stick, Mentoring and Production Monitoring); and 3) Evaluation Stage (Evaluation of sales of stick stick). The result of this activities is obtained a best tempe stick formula with the composition of raw material is wheat (45.0), tempe (45.0), margarine (3.6), lime leaves (1.5), baking powder (0.1), salt (0.6), and water (3.0) with nutrient content per 100 gr tempe stick is energy (464 kcal), water (4.96 g), protein (13.03 g), fat (19.47 g), and carbohydrate (59.08 g). Capital per pack business (100 g) of IDR 3.742 with the selling price of IDR 8.000, then the profit of IDR 4.258 per pack (113.8%). Based on the results of these activities it can be concluded that tempe stick is a nutritious snack food that is feasible to be developed as a profitable business branch.